Analisis Ketidakadilan Gender Terhadap Tokoh Perempuan Laura dalam Film Laura Menggunakan Kajian Feminisme - Rahmadini, Suci Nur; Alsunah, Aditya Ansor; Nurwahidah, Lina Siti (Asosiasi Ide Bahasa Kepri, 2025)
The aim of the research is to analyze the forms of gender injustice experienced by the female character Laura in the film Laura through the lens of feminist studies. This study is grounded in the understanding that films often reflect and reinforce gendered power relations, making them important cultural texts for examining women’s experiences of oppression. Feminist theory provides the conceptual basis for identifying how patriarchal structures are represented and how they shape the narrative surrounding female characters. This research uses a qualitative descriptive-analytical method to explore scenes, dialogues, and narrative elements that construct Laura’s experiences. Data were collected using documentation techniques by identifying and recording film segments that indicate gender injustice. The analysis focuses on key feminist concepts such as marginalization, violence, subordination, and the reduction of female agency. Through this framework, the study interprets not only the visible acts of injustice but also the symbolic meanings embedded in the film’s portrayal of Laura. The findings indicate that Laura encounters various forms of gender injustice, including five instances of marginalization and four instances of violence. These portrayals reveal how the film reproduces patriarchal patterns that position women as vulnerable and socially limited. Cinematic elements—such as framing, narrative emphasis, and emotional depiction—further reinforce Laura’s disadvantaged position within the storyline. Overall, this study contributes to feminist film analysis by showing how Laura perpetuates gender-biased representations that restrict female autonomy. The research underscores the importance of feminist perspectives in uncovering power imbalances and promoting more equitable portrayals of women in contemporary media.